The Relationship of Innovation Capabilities Towards Employees’ Perormance: Mediating Effect of Cultural Diversity in UAE Manufacturing Companies - Md Fauzi Ahmad; Hamdan Sohail Obaid Alhefeiti; Mohd Nasrun Mohd Nawi; Arman Shah Abdullah (International Journal of Supply Chain Management, 2019)
Innovation capabilities of employees was considered as the main strategic activity of administered as a means of objective assessment of the individual performance of various professionals in MOI UAE. This study first aimed to identify whether employees’ innovation capabilities in MOI would exhibit better performance in UAE. Secondly, this study also aimed to identify the theoretical issues related with cultural and technological diversity with individual innovation capabilities and gave the ways to improve their performance in MOI UAE setting. This study proposes a conceptual framework for understanding innovation process and knowledge management aspects of innovation capability which would influence individual performance. The conceptual framework includes cultural diversity as mediating variable in the effect of innovation capability which would influence individual performance. The conceptual carry out through empirical review of literature and development of hypothesis. The adaption of well-structured questionnaire used in this study. The study also validates the proposed conceptual framework using a second-order confirmatory factor analysis technique, namely, structural equations modelling, with the data collected from 607 followers from 6 MOI departments in the UAE.